Pandemic COVID-19 And Consumer Behavior: Moderation And Mediation Of Socioeconomic Factors - Abdelkhair, Farah Y. F.; Soharwardi, Mariam A.; Mazrou, Yasser S. A.; Mudawi, Sara S. A.; Ashraf, Ijaz; Ashraf, Saleem; Mohammad, Reda A. (Migration Letters, 2024)
COVID-19 has rapidly affected consumer behaviour and perception towards risk decisions. The variations in consumer behaviour have consequences on everyday life during and after the lockdown. A comprehensive theoretical and conceptual framework of consumer behaviour during the pandemic COVID-19 has been developed which was supported through grand models of consumer decision-making, facing situations during and after COVID-19, household members, income factors, employment status, education and gender which was collected by survey. Such a type of survey has not been conducted in previous literature. Consumer behaviour is measured through a multi-dimension index (health, education, daily and large households’ purchases) using the principal factor analysis. Results showed that all the social and economic factors have different effects on consumer behaviour during the lockdown. It demonstrates that after lockdown it would be very difficult to normalize consumer behaviour in the business sectors. For the sake of growth in the business sector, it is necessary to address all these fluctuations in consumer behaviour. The households of the districts Bahawalpur and Rahim Yar Khan of Pakistan were selected as the target population for the study. Primary Through the use of a questionnaire & randomly stratified test, data from 300 families were obtained. Approximate least[1] squares and quantitative approaches were used to evaluate the data. All results have been proven experimental and stated the situations faced during COVID-19 have positively and significantly affected consumer behaviour and these results followed with grand models as education, income factors, gender and employment status have significantly affected consumer behaviour directly or indirectly. Similarly, employment status, education, marital status, gender and household members have a favourable and substantial impact on the circumstances faced during COVID-19 and income factors played the mediating role. The current study concluded that the pandemic COVID-19 changed consumer behaviour along with social and economic factors during and after the lockdown.